Comprehensive Comparison of Ultra-low Emission Coal-Fired Power Plants and Gas-Fired Power Plants - Jingxin XU; Fahua ZHU; Sheng WANG; Ming ZHANG; Xiuyong ZHAO; Xueli SUN; Yun HU; Wenxin TIAN (Zhongguo dianli)
Coal-fired and gas-fired power generation are the two major types of thermal power generation in China. This paper compares ULE coal-fired power plants with the gas-fired power plants from three aspects, i.e., technologies, environmental effect and economic benefit. The comparison results show that firstly, the power generation and pollution control technologies for ULE coal-fired power plants have been developed and manufactured completely and independently with the overall technologies reaching the global advanced level, while for gas-fired power plants key technologies are still imported abroad such that the technology development including gas turbine manufacturing need to speed up. Secondly, in terms of environmental effects, ULE coal-fired power plants have achieved effective control over the gas, liquid and solid emission of conventional pollutants with very few impacts on the environment, which means they are even much more cleaner than gas-fired power plants as long as their standard coal consumption is not higher than the national average value. At last, in terms of economic benefits, ULE coal-fired power plants continue to maintain significant economic advantage over gas-fired power plants. These results can provide not only the theoretical reference for the evaluation of the pros and cons of the two types of power plants in an objective way, but also necessary basis and suggestions for the formulation of national polices.